KAJIAN YURIDIS TENTANG EKSPLOITASI ANAK SEBAGAI PEMERAN IKLAN DALAM SIARAN IKLAN NIAGA - Pratama, Radhyca Nanda (Universitas Negeri Surabaya, 2020)
Children are one of the vulnerable groups based on the explanation of Article 5 paragraph (3) of Law of the Republic of Indonesia Number 39 of 1999 on Human Rights. The involvement of children as an actors is often found in many commercials on television. Such matter that has attracted attention is the involvement of children as ad actors, whether it can be categorized as acts of exploitation against children. This research aims to analyze the concrete limits on exploitation and / or exceptions so that when a child is involved in an advertisement, it is not categorized as exploiting. Furthermore, to analyze the form of legal protection for children related to differences in the age of children in terms of a ban on the exploitation of children in commercial broadcasts. The selection of this type of research is based on the legal vacuum namely there are no exclusionary restrictions related to the exploitation of children used as advertising actors and asynchronous related to children's age restrictions on the prohibition of children being exploited as advertising actors in commercial ad broadcasts. The approaches used in this research is the statutory approach and the concept approach. The results of the research are based on argumentum per analogiam, then the limits on the exploitation of children are subject to the provisions of Article 69 of Law of the Republic of Indonesia Number 13 of 2003 on Manpower. The application of the principle of lex superior derogate legi inferiori, which is Law of the Republic of Indonesia Number 32 of 2002 on Broadcasting overrides KPI Regulation No. 02 / P / KPI / 03/2012 so that the age limit of children as advertising actors is 18 (eighteen) years and legal protection based on several applicable laws.